Patterns of success amongst Hungarians living in the UK (Szociológiai Szemle, 2023)
This paper investigates the characteristics of Hungarian migration into the UK, the distinctive features of different migrant groups, and the chances for perceived individual success. The study is based on an on-line study conducted in 2014, using a large sample, albeit a non-representative method of data collection. By presenting the results related to migration to the UK, one can have a broader picture on present day migration starting from Hungary. The study demonstrates that migration from Hungary is neither a straightforward, nor a mono-dimensional process: migrants abroad form a diaspora in a transnational environment that maintains several links to their country of origin. Professional development, fulfilling individual potential, and career-mobility all play a very important role in migration. A significant number of migrants consider migration a success, and experience upward mobility while changing their places of residence. Venturing out from the ethnic “niche” seems to bring better networking resources and more openness, which further contributes to migrants’ success. There seems to be a strong correlation between success in the new country and the frequency of visits to the country of origin: this might be exploited by a dynamic diaspora politics that regards migrants abroad an important resource of the country.